Opening Up Hispanic Literature: An Open-Access Critical Edition Assignment - Julie Ann Ward; Madison Doyle (Park University, 2020)
Pedagogical research into cooperative learning and open educational resources supports an expectation for strong learning outcomes in both cases. This article is a guide to the implementation of a group assignment in a college introductory Hispanic literature course where students create critical editions of literary texts. The critical editions project described in this article focuses on team-building and training in group dynamics in addition to the skills of literary research. This project's relationship to the Open Education movement is an important part of its success, in that it both uses Open Educational Resources (OER) through public domain literary texts as the objects of study in the course, and also asks students to produce OER through their critical editions of literary texts in the public domain. In this essay, we describe a group activity in which students in an introductory literature course research and create digital critical editions of literary texts, which are in turn collected and published online in an open-access anthology. Over the course of a semester, students are engaged in establishing and maintaining group dynamics, learning the basic skills of literary research, and presenting their research findings with the goal of creating a public good.